Clinical Spectrum and Determinants of Acute Exacerbations in Chronic Obstructive Pulmonary Disease (COPD) in Urban Pakistan - TALHA SADIQ, MUAAZ BIN SAIF, ALEENA NAZAR, MAIRA IQBAL, URVAH TARIQ, LABIQA AFZAAL, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are a major cause of morbidity, hospitalization, and mortality worldwide. In urban Pakistan, rapid urbanization, high smoking prevalence, air pollution, biomass fuel exposure, and suboptimal preventive care may significantly influence the clinical presentation and determinants of AECOPD. Objective: To evaluate the clinical spectrum of AECOPD and identify key determinants associated with frequent and severe exacerbations among COPD patients in an urban Pakistani setting. Methods: This hospital-based observational study was conducted at Arif Memorial Teaching Hospital and Shaikh Zayed Hospital, Lahore, from May 2023 to April 2024. A total of 120 adults with physician-diagnosed COPD presenting with acute exacerbations were enrolled. Demographic data, clinical features, smoking and environmental exposures, comorbidities, inhaler adherence and technique, vaccination status, and exacerbation history were recorded. Severity outcomes included hospitalization, need for non-invasive ventilation (NIV), intensive care unit admission, and in-hospital mortality. Multivariable logistic regression analysis was performed to identify independent determinants of frequent (≥2/year) and severe exacerbations. Results: The mean age was 61.4 ± 9.8 years; 68.3% were males and 31.7% females. Frequent exacerbations were observed in 45% of patients. Hospitalization was required in 65%, NIV in 28.3%, and ICU care in 14.2% of cases. Independent predictors of frequent and severe AECOPD included current smoking, poor inhaler adherence, incorrect inhaler technique, lack of influenza vaccination, biomass fuel exposure, prior hospitalization for AECOPD, radiological pneumonia, and ischemic heart disease. Conclusion: AECOPD in urban Pakistan is commonly severe and largely driven by preventable and modifiable factors. Strengthening preventive care, patient education, and integrated management strategies is essential to reduce exacerbation burden and improve outcomes. Keywords: Chronic obstructive pulmonary disease; Acute exacerbation; Urban Pakistan; Smoking; Biomass fuel exposure; Inhaler adherence; Vaccination.